Analysis of the crime of femicide suicide in Latinamerica and Spain. Is the difinition necessary? - Machuca Moreno, Leslit Estefany (2023)
The pandemic caused by covid-19 has had a big impact on human health rights. This is internationally recognized as a human right, which guarantees people to live and enjoy their life. The legal systems of different countries have recognized the protection of the right to health and have established it as an obligation of public powers and state institutions so that citizens can make use of and access their rights, without any restriction. In many countries, such as in the case of Ecuadorians, many distinct constitutional actions can be brought up, such as: protection actions, cultural means or extraordinary actions to help prevent, mitigate the effect of this right. In the Spanish case, the right to health is considered like a principal to the economy and it can be seen bonded to many fundamental rights such as: the physical integrity and life, which in the case of an effect to the right to health it could interpose an appeal for protection of fundamental rights so that it indirectly grants protection to health. With the appearance of Covid-19, it was verified that it was not only necessary the activation of the judicial constitutional channel to make this right effective. Since the sanitary crisis searched for other solutions to prevent the spread of the virus. Thus, each state had distinct governmental challenges, which obligated and forced them to take immediate and urgent actions which were necessary to prevent and stop the massive contagion. Despite all the measures taken, the sanitary system was seen to be collapses due to several social and economic factors. This has served as a base to reinforce and establish strong public policies, which will allow in the future to deal with any similar situation.